Estimation of Hydropower Harvesting from the Hydraulic Structures on Rivers: Ramadi Barrage, Iraq as a Case Study - ., Omar Sulaiman Abdullah; ., Ammar Hatem Kamel; ., Wissam Hashim Khalil; ., Amer Al-damook (Iraqi Journal of Civil Engineering, 2022)
In recent years, Iraq suffers from exacerbation of the deficit of electrical energy as well as the great environmental pollution resulting from the use of traditional fuels. This called for serious thought to search for using clean and renewable energy sources may available in Iraq.In the present study; small hydropower (i.e. Archimedes screw turbine) are specifically used with a low head at Ramadi Barrage in Iraq. This type of small hydropower station is suitable to apply because not need high storage water or high head in Barrage. The power production in this technology depends on the parameters of the location in which it is placed such as (length L, angle of inclination α, Diameter D,….). The physical model of the Archimedes screw turbine is applied to determine the optimal α. The solid work package with a combination of Computational Fluid Dynamics (CFD) analysis by ANSYS have been used to simulate numerically a three dimensions model to determine the value of power that could be produced by the Archimedes turbine in the Ramadi Barrage. The turbine’s performance are tested on two cases which represent low and high discharge investigations with different α (18⁰, 23⁰, 30⁰, 35⁰) based on different flow conditions and different water head between upstream and downstream of the barrage. The results showed that the maximum power production from the barrage is 280,000 watts with α=35° and efficiency η=89.9% for case 1; while; this power becomes 400,000 watts with α=30° but of efficiency η=84.9% for case 2. It is concluded from this research that power production from Ramadi Barrage could be investment to eliminate the deficit in the electrical energy in Iraq.